Porokeratosis Plantaris, Palmaris Et Disseminata - Chatterjee Tapas Kumar; Sadhu Sisir Kumar (Wolters Kluwer Medknow Publications, 1997)
A 14 year old girl developed dark, keratotic lesions all over the body for the last 9 years. The lesions were mostly linear but some were oval with keratotic border and atrophied center. The lesions were almost symmetrical in distribution. Homy and warty lesions appeared over soles for the last 2 years. An unusual presentation of porokeratosis plantaris, palmaris to disseminata is described.